The biodiversity of black flies (Diptera: Simuliidae) in Indonesia - Hadi, Upik Kesumawati; Takaoka, Hiroyuki (Elsevier, 2018)
Indonesia is one of the megadiversity country in the world endowed with rich and unique biodiversity insects such as blackflies species (Diptera: Simuliidae). Blackflies are found almost anywhere with running water suitable as habitat for the immature stages. This family is one of the most important groups of blood-sucking insects. This study collates the records of Simulium (Diptera: Simuliidae) in previous publications related fauna of Indonesia. Based on the results of this study, there were 124 species of blackflies in Indonesian Archipelago. All species are assigned to the genus Simulium Latreille s.l., and are placed into five subgenera, i.e. Gomphostilbia Enderlein, Morops Enderlein, Nevermannia Enderlein, Simulium Latreille s.str. and Wallacellum Takaoka. Further classification into 27 species groups within the subgenera were also made. Checklists of Indonesian Simuliidae are provided including data on the distribution of each species.